A Socioeconomic Analysis of Property Assessment Uniformity: Empirical Evidence on the Role of Policy. (17th March 2013) - ROSS, JUSTIN M.
Abstract Though property assessment uniformity has been repeatedly studied as a technical problem related to the difficulty of the task, popular, and policy sentiment against the property tax is frequently directed at the incidence of nonuniformity across socioeconomic groups. Using data from Virginia, this paper brings socioeconomic determinants to the forefront of the analysis and their interaction with policy. Unlike the previous literature that employs controls for the time passed since the last reassessment, this paper consider show policy and socioeconomic variables may exert different influences between assessments. For example, the results indicate that elected and appointed assessors perform similarly during mass reappraisals in terms of maintaining uniformity, but appointed assessors perform far better during nonassessment years.